In vivo anti-obesity effects of Monascus pigment threonine derivative with enhanced hydrophilicity. (April 2020) - Choe, Deokyeong; Jang, Heeyoung; Jung, Hyun Ho; Shin, Chul Soo; Johnston, Tony V.; Kim, Daehwan; Ku, Seockmo
Graphical abstract: Highlights: A threonine derivative of Monascus pigment with enhanced hydrophilicity was synthesized. The synthesized threonine derivative reduced body weight gain, epididymal fat weight and abdominal fat size in mice. The threonine derivative lowered serum lipid levels in a concentration-dependent manner. The threonine derivative caused little to no change in organ weights of mice. Abstract: The hydrophobicity and anti-obesity characteristics of the threonine (Thr) derivative of Monascus pigment were determined and compared with 2-( p -tolyl)-ethylamine (TEA) and tryptophan (Trp) derivatives of the same. Treatment by all three derivatives decreased body weight gain, epididymal fat weight, and abdominal fat in mice. The lowest body weight gain and epididymal fat weight were observed with the Monascus -Thr derivative treatment, which is more hydrophilic than other the other treatments tested. Further in vivo tests with the Thr derivative at different concentrations demonstrated that body weight, epididymal fat weight, and serum lipid level are reduced in a concentration-dependent manner. Significant reduction was exhibited at 0.10 mg/g-mouse/day of the Thr derivative, and less reduction was observed at 0.05 or 0.01 mg/g-mouse/day. In comparison with mice fed a normal diet, there was no statistical weight change in the liver, kidney, or spleen, indicating the Thr derivative was not toxic to mice.